Who are appropriate surgical candidates among patients with oligometastatic non-small cell lung cancer? - Hishida, Tomoyuki (Journal of Thoracic Disease; Vol 9, No 2 (February 28, 2017): Journal of Thoracic Disease, 2017)
Metastasis of cancer should be microscopically present in the systemic circulation, which justifies the need for systemic chemotherapy. Although systemic chemotherapy can improve survival relative to supportive care, for the vast majority of patients, disease progression occurs and a cure cannot be achieved.